Variety aversion and information overload: An experimental approach - Karen Kaiser (Banco de México, 2011)
This paper analyzes the effect of information overload on preference or aversion for variety. According to the model, a rational decision maker who suffers from information overload, faces a two-stage decision process, and is choosing from a set of unknown goods will find it optimal at some point to become variety averse. To test this hypothesis, an experiment is conducted, and its results, that subjects suffering from information overload use variety aversion as a strategy to deal with their cognitive limitations, are consistent with the model. Moreover, results suggest that subjects are, on the average, choosing the optimal number of goods. As the price of the goods increases, subjects become more variety averse. In addition, as they become more experienced, they prefer larger sets of goods.
Keywords: C91; D81; D83; 330; variety aversion; information overload; bounded rationality; decision making; laboratory experiment